Evaluation of One-Sided Percentage Points of the Singular Multivariate Normal Distribution - KWONG, Koon Shing (Institutional Knowledge at Singapore Management University, 1995)
This paper presents a new theorem, as a substitute for existing results which are shown to have some errors, for evaluating the exact one-sided percentage points of the multivariate normal distribution with a singular negative product correlation structure. By extending the result from the multivariate normal distribution to the multivariate t-distribution with corresponding singular correlation structure, we tabulate the one-sided critical points for the Analysis of Means procedure.